EFFECT OF BREAD YEAST (SACCHAROMYCES CEREVISEAE) CONCENTRATION AND FERMENTATION TIME IN THE MANUFACTURE OF BIOETHANOL USING BANANA PEEL - Febriana, Ida (Jurnal Distilasi, 2018)
Energy needs that are developing at this time are not comparable with the increasing availability of fuel that is running low. Therefore, a study is needed to obtain alternative sources of renewable energy by utilizing biomass waste such as banana peels and so on. In this study, the raw material used was banana peel waste in the industrial area processing bananas that had been taken, and the skin was left to rot and become organic fertilizer. The purpose of this research is to determine whether there is influence of banana skin type to bioethanol content, influence of yeast concentration and fermentation time in bietanol manufacture using banana peel. Based on the research results can be seen that the hights % alcohol content is found in banana peel batu (musa balbisiana)samples with the addition of yeast weight ± 0.0720 gr of 13.6451% then banana peel kepok (musa paradisiaca L) and banana peel raja (musa sapientum) with each % alcohol content of 13.5353% and 12.9953%